Macrophage Fc receptors control infectivity and neutralization of canine distemper virus-antibody complexes. - Appel, M J (1984)
Dogs that are persistently infected or that become moribund after exposure to canine distemper virus (CDV) have antibody that neutralized CDV when tested in dog lung macrophage cultures but failed to neutralize CDV when tested in epithelial, fibroblastic, or lymphatic cells. The antibody attached to protein A and was found in the immunoglobulin G fraction. The antibody bound complement and lysed CDV-infected target cells. The neutralizing activity in macrophages could be abolished (i) by pepsin digestion and removal of Fc portions from the antibody, (ii) by blocking the Fc receptors of macrophages with heat-treated normal dog serum, and (iii) by binding of protein A to Fc portions of the antibody. It was concluded that attachment of the CDV-antibody complex to Fc receptors of macrophages was essential for virus neutralization. If this attachment was hindered, the CDV-antibody complex became infectious for macrophages. In contrast, serum from recovering dogs neutralized CDV when tested in epithelial, fibroblastic, or lymphatic cells as well as in macrophages.